2023
DOI: 10.1080/19490976.2023.2238959
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Metabolic Associated Fatty Liver Disease by Protocatechuic Acid

Abstract: Gut microbiota–diet interaction has been identified as a key factor of metabolic associated fatty liver disease (MAFLD). Recent studies suggested that dietary polyphenols may protect against MAFLD by regulating gut microbiota; however, the underlying mechanisms remain elusive. We first investigated the effects of cyanidin 3-glucoside and its phenolic metabolites on high-fat diet induced MAFLD in C57BL/6J mice, and protocatechuic acid (PCA) showed a significant positive effect. Next, regulation of PCA on lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…13,30,31 The high fiber diets potentially reduced the blood glucose levels through remodeling the gut microbes in the current study, and might act on glucose and lipid metabolism. 32–34 Therefore, in this study, high dietary fiber contents improved the glucose response in the healthy mouse models, although the body weight and feed intake of mice was not significantly altered. However, the limitation was that we did not detect changes to the insulin levels therefore we cannot directly declare that the insulin activity was changed by high fiber diets in this study.…”
Section: Discussionmentioning
confidence: 58%
“…13,30,31 The high fiber diets potentially reduced the blood glucose levels through remodeling the gut microbes in the current study, and might act on glucose and lipid metabolism. 32–34 Therefore, in this study, high dietary fiber contents improved the glucose response in the healthy mouse models, although the body weight and feed intake of mice was not significantly altered. However, the limitation was that we did not detect changes to the insulin levels therefore we cannot directly declare that the insulin activity was changed by high fiber diets in this study.…”
Section: Discussionmentioning
confidence: 58%
“…3G) suggested a potential alteration in the ratio of Firmicutes/Bacteroidota induced by alcohol consumption, which was effectively counteracted by L. plantarum P101 intervention. In a study conducted by Tan et al , 32 mice afflicted with metabolic associated fatty liver disease exhibited an elevated Firmicutes/Bacteroidota ratio. Notably, the ratio was effectively restored to the levels similar to that of the control group through protocatechuic acid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that gut microbes play a critical role in the occurrence and development of metabolic liver disease. 43,44 It has been reported that chronic alcohol intake impairs intestinal microbiota homeostasis and biological barrier, which contribute to the pathological process of ALD through the gut-liver interaction system. 45 Dietary patterns are closely related to gut microbiota homeostasis.…”
Section: Discussionmentioning
confidence: 99%